Brain-Derived Neurotrophic Factor Modulates Nociceptive Sensory Inputs and NMDA-Evoked Responses in the Rat Spinal Cord - Kerr, B. J. (J Neurosci, 1999)
Central sensitization, the hyperexcitability of spinal processing that often accompanies peripheral injury, is a major component of many persistent pain states. Here we report that the neurotrophin, brain-derived neurotrophic factor (BDNF), is a modulator of excitability within the spinal cord and contributes to the mechanism of central sensitization. BDNF, localized in primary sensory neuron cell bodies and central terminals, potentiates nociceptive spinal reflex responses in an in vitro spinal cord preparation and induces c-fos expression in dorsal horn neurons. NMDA receptor-mediated responses, known as a major contributor to central sensitization, were significantly enhanced by exogenous BDNF. Systemic NGF treatment, a procedure that mimics peripheral inflammatory states, raises BDNF levels in sensory neurons and increases nociceptive spinal reflex excitability. This increased central excitability is reduced by trkB-IgG, a BDNF “antagonist.” We also show directly that inflammatory pain-related behavior depends on BDNF release in vivo. Thus behavioral nociceptive responses induced by intraplantar formalin and by intraplantar carageenan are significantly attenuated by trkB-IgG. Hence BDNF is appropriately localized and regulated in inflammatory states and is sufficient and necessary for the expression of central sensitization in the spinal cord. We propose that BDNF may function as a modulator of central sensitization in pathological states, and our results suggest that pharmacological antagonism of BDNF may prove an effective and novel analgesic strategy for the treatment of persistent inflammatory pain states.